Long working relationship with Nurses' Level Of Nowledge About Diabetes Mellitus Management In Hospital St. Elisabeth Semarang - Maria Karolina Selano; Rina Dwi Pangesti; Freaty Ayu Agustina; Laurentius Denis Satria (Science Midwifery, 2022)
Diabetes Mellitus (DM) is a disorder of carbohydrate, protein and fat metabolism characterized by hyperglycemia or increased levels of glucose in the blood caused by abnormalities in insulin secretion or decreased insulin action. Hyperglycemia can adversely affect various organs of the body such as diabetic neuropathy, foot ulcers, diabetic retinopathy, diabetic nephropathy and blood vessel disorders. Complications due to uncontrolled blood sugar can result in high morbidity rates that can affect the quality of life of the sufferer. The increasing prevalence of diabetes mellitus (DM) shows the importance of prevention efforts. DM management consists of pharmacological and non-pharmacological therapy. One of the non-pharmacological therapies is changing the behavior of DM patients. So it takes active education from nursing staff who help the nursing process for 24 hours in the hospital. The provision of education by nurses depends on the desire and ability of a nurse to provide education, and is supported by the level of knowledge of the nurse about diabetes mellitus management. This study aims to determine the length of work with the level of knowledge of nurses about diabetes mellitus management.This research is a quantitative research with a cross sectional study design. Data were collected with a questionnaire about the length of work and knowledge of nurses about diabetes mellitus management. The study was conducted from November to December 2021 with a sample size of 60 respondents. The sampling method in this study used purposive sampling in accordance with the inclusion and exclusion criteria. The source of data in this study is primary data. The population of this study were nurses in the inpatient ward of St. Elisabeth Semarang.